2019
DOI: 10.1016/j.redox.2018.101082
|View full text |Cite
|
Sign up to set email alerts
|

Lipids and lipoxidation in human brain aging. Mitochondrial ATP-synthase as a key lipoxidation target

Abstract: The human brain is a target of the aging process like other cell systems of the human body. Specific regions of the human brain exhibit differential vulnerabilities to the aging process. Yet the underlying mechanisms that sustain the preservation or deterioration of neurons and cerebral functions are unknown. In this review, we focus attention on the role of lipids and the importance of the cross-regionally different vulnerabilities in human brain aging. In particular, we first consider a brief approach to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 109 publications
1
48
0
Order By: Relevance
“…Several anti-oxidative factors such as glutathione (GSH), superoxide dismutase (SOD) and glutathione peroxidase (GPx) regulate the levels of ROS that are mainly generated by the mitochondrial respiratory chain [28][29][30][31]. In the cytosol, enzymes such as amino acid oxidases, cyclooxygenases, lipoxygenases, nitric oxide (NO) synthase, and xanthine oxidase also generate ROS such as superoxide anions, peroxides and others [32][33][34].…”
Section: Oxidative Stressmentioning
confidence: 99%
“…Several anti-oxidative factors such as glutathione (GSH), superoxide dismutase (SOD) and glutathione peroxidase (GPx) regulate the levels of ROS that are mainly generated by the mitochondrial respiratory chain [28][29][30][31]. In the cytosol, enzymes such as amino acid oxidases, cyclooxygenases, lipoxygenases, nitric oxide (NO) synthase, and xanthine oxidase also generate ROS such as superoxide anions, peroxides and others [32][33][34].…”
Section: Oxidative Stressmentioning
confidence: 99%
“…Furthermore, it underscores the impact of neural dysfunction in the loss of smell at aging, beyond the changes occurring in the olfactory epithelium over time. In P. leucopus, processes associated with lipid metabolism were suggested that may reflect adaptive responses due to the aging-associated loss of lipid content in the brain [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Phospholipids are structurally and functionally important cell membrane constituents. Numerous studies have been conducted to examine their role in aging [ 40 ], as phospholipids are the primary functional components of neuronal membranes [ 41 ]. These results suggest that PLDP represents a promising nutraceutical that could improve cognitive function in healthy adults over 40 years of age.…”
Section: Pldp and Cognitive Improvementmentioning
confidence: 99%